Hubungan Aktifitas Fisik dengan Kejadian Obesitas Pada Remaja Putri di SMAN 2 Penebel - Kadek Yeni Prihandani; Ni Komang Yuni Rahyani; Ni Ketut Somoyani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Background: Obesity among adolescent girls is a growing public health concern associated with physical and psychological problems. One of the contributing factors is insufficient physical activity. Objective: To determine the relationship between physical activity and obesity among adolescent girls at State Junior High School 2 Penebel. Methods: This analytical observational study employed a cross-sectional design. A total of 46 participants were selected using simple random sampling. Data were collected from February to March 2026 and analyzed using Spearman’s rho test with a significance level of p < 0.05. Results: All participants were 14 years old, with a mean body weight of 52.98 kg and a mean height of 154.56 cm. Most respondents had light physical activity (73.9%), while 67.4% were not obese. Spearman’s rho analysis showed a significant relationship between physical activity and obesity (p = 0.036). Conclusion: Physical activity was significantly associated with obesity among adolescent girls at State Junior High School 2 Penebel. Healthcare workers are encouraged to provide education on physical activity and obesity prevention through engaging media, such as Reels or short animated videos.